2015
DOI: 10.1021/id500033m
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cholesterol Catabolism in Mycobacterium tuberculosis: ChsE4-ChsE5 α2β2 Acyl-CoA Dehydrogenase Initiates β-Oxidation of 3-Oxo-cholest-4-en-26-oyl CoA

Abstract: The metabolism of host cholesterol by Mycobacterium tuberculosis (Mtb) is an important factor for both its virulence and pathogenesis, although how and why cholesterol metabolism is required is not fully understood. Mtb uses a unique set of catabolic enzymes that are homologous to those required for classical β-oxidation of fatty acids but are specific for steroid-derived substrates. Here, we identify and assign the substrate specificities of two of these enzymes, ChsE4-ChsE5 (Rv3504-Rv3505) and ChsE3 (Rv3573c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 55 publications
2
93
0
Order By: Relevance
“…Consistent with the idea that lipids are important nutrients the early genome annotation efforts revealed that M. tuberculosis has an expanded repertoire of genes associated with lipid metabolism and β-oxidation, which exceeded 250 genes (57). Although several of the M. tuberculosis genes originally annotated as having a β-oxidation functions are now known to have anabolic activities (58, 59) or act in multimeric complexes to oxidize lipids (60, 61) the M. tuberculosis genome still encodes more genes involved in lipid metabolism and β-oxidation relative to other bacteria. Another critical pathway that is required when bacteria metabolize lipids is the anaplerotic glyoxylate cycle and a key enzyme in this pathway is isocitrate lyase (Icl).…”
Section: Lipid Utilization By M Tuberculosis In Macrophagesmentioning
confidence: 99%
“…Consistent with the idea that lipids are important nutrients the early genome annotation efforts revealed that M. tuberculosis has an expanded repertoire of genes associated with lipid metabolism and β-oxidation, which exceeded 250 genes (57). Although several of the M. tuberculosis genes originally annotated as having a β-oxidation functions are now known to have anabolic activities (58, 59) or act in multimeric complexes to oxidize lipids (60, 61) the M. tuberculosis genome still encodes more genes involved in lipid metabolism and β-oxidation relative to other bacteria. Another critical pathway that is required when bacteria metabolize lipids is the anaplerotic glyoxylate cycle and a key enzyme in this pathway is isocitrate lyase (Icl).…”
Section: Lipid Utilization By M Tuberculosis In Macrophagesmentioning
confidence: 99%
“…Microbial transformation could be carried out under mild reaction conditions with excellent yields of products and remarkable regio- and stereo-selectivity, which is hardly available for chemical synthesis. Therefore, for producing novel steroidal drugs and generating active pharmaceutical ingredients, microbial transformation is employed as a novel, efficient and economical tool (Donova 2007; García et al 2012; Yang et al 2015). For example, side chains of phytosterol, a byproduct from soybeans, sugar and paper industries, can be selectively degraded by a process similar to the β-oxidation of fatty acids, yielding 17-ketosteroids (Wei et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of enzymatic processes and purity of their products have obvious advantages in comparison with multi-steps chemical syntheses of hormonal drugs. However, the development of steroid biotechnology requires further studies of microorganisms able to degrade/modify steroids as well as enzymes catalyzing these reactions on the molecular level (Yang et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…FadD19 is an essential enzyme when Mtb is grown on cholesterol 16 and is the only fatty CoA ligase that has been identified to esterify the terminal cholesterol carboxylic acid. However, FadD19 is not stereoselective as it accepts both the 25 R and 25 S carboxylic acids 6 (Scheme 1). Thus, the metabolic pathway that Mtb utilizes to activate cholesterol to its CoA ester provides both the 25 R or 25 S diastereomers of 3-oxo-cholest-4-en-26-oyl CoA (3-OCS-CoA).…”
mentioning
confidence: 99%
“…5, 6, 8, 9 ChsE4-ChsE5 is the only ACAD protein regulated by KstR1 that can oxidize 3-OCS-CoA the first acyl-CoA metabolite in the side chain β-oxidation cycle. 6 …”
mentioning
confidence: 99%